Lebensmitteldiscounter und Supermarkt. Untersuchung zu Verkehrseffekten, Einzugsgebieten, Vorlieben der Kunden und zum Genehmigungsprozess vor dem Hintergrund der Regelungen des § 11 Abs. 3 BauNVO - Anders, Sascha (Raumforschung und Raumordnung | Spatial Research and Planning, 2015)
For the location of new food markets in Germany, the provisions of article 11 sector 3 BauNVO (Federal Land Utilisation Ordinance) and the corresponding jurisdictions are of great importance. The expected impacts of new markets are always object of controversial discussions. Against this backdrop, the study on qualified local supply, based on a nationwide household survey conducted by telephone, analyzed among others the catchment areas and traffic impacts of the different types of business in food retail — in correlation with the demands and preferences of customers. Unlike common surveys, related to a particular case and carried out within the course of urban land-use planning considerations, the presented study tries to provide general evidence. This shall provide the responsible public authorities and agencies of public interest with a reliable basis for necessary considerations and the balance of interests. Our empirical studies show that the in article 11 sector 3 BauNVO formulated general presumption of urban impacts from a sales area of 800 m2 onwards cannot be confirmed — at least not for the food retail sector. But there also is no other empirically robust sales area limit instead. Besides the size of the market especially the location of the market (urban integrated vs. non-integrated), the urban framework (urban vs. rural) and the different retailers themselves (like Aldi, Edeka) have a crucial influence on traffic impacts and purchasing power levies.